MANAJEMEN KEPEMIMPINAN INOVATIF KEPALA SEKOLAH DALAM MENINGKATKAN KUALITAS IMPLEMENTASI KURIKULUM MERDEKA DI SD NEGERI TEBO - Rosita, R; Rahayu, Sri (Fakultas Ekonomi dan Manajemen, 2025)
This study aims to analyze the role of innovative school leadership in improving the quality of the implementation of the Merdeka Curriculum at SD Negeri Tebo, Poto Tano District, West Sumbawa Regency. The Merdeka Curriculum requires teachers to be more creative and adaptive in the learning process, making the principal’s role strategic in facilitating, guiding, and motivating teachers to effectively apply the curriculum principles. This study employs a descriptive qualitative approach, using data collection techniques through in-depth interviews, classroom observations, and documentation. Data analysis was conducted through stages of data reduction, data presentation, and drawing conclusions to gain a comprehensive understanding of the principal’s leadership practices and their impact on the quality of learning. The results show that the principal applies innovative leadership through routine supervision, teacher mentoring, and fostering a collaborative culture among teachers. These leadership strategies encourage teachers to implement creative learning methods, utilize media and digital technology effectively, and conduct continuous evaluations of the learning process and student outcomes. The participative and adaptive leadership applied by the principal has proven to enhance teacher motivation, student engagement, and overall learning quality. The findings indicate that innovative leadership management is not only administrative but also strategic, collaborative, and focused on improving learning quality. This study provides important implications for teacher professional development, optimizing the role of school principals, and educational policies to support the successful implementation of the Merdeka Curriculum in elementary schools.